Fish food-web structure of a southern Mediterranean lagoon (El Mellah Lagoon, Algeria): what we can learn from stable isotope analysis - DENIS, JEREMY; BOUAZIZ, RYM; DRAREDJA, BRAHIM; MUNARON, JEAN MARIE; BORHANE DJEBAR, ABDELLAH; AMARA, RACHID; LE LOC’H, FRANÇOIS; BEN RAIS LASRAM, FRIDA (Mediterranean Marine Science, 2023)
The structure of a fish food-web was described for the first time in a coastal lagoon in the southern Mediterranean Sea by analysing stable carbon and nitrogen isotopes of fish species and their potential food sources. The El Mellah Lagoon (EML) located in extreme north-eastern Algeria, is the only coastal lagoon in the southern Mediterranean with low human pressure due to few human activities and its protected status under the Ramsar Convention. We investigated the structure of the fish food-web in the spring at four stations in the lagoon that differed in their proximity to rivers and the channel, which connects to the sea. The results provided insight into ecological functions of EML as a feeding area for all fish species caught in the lagoon, in particular marine migrant juveniles and resident species. The δ13C results highlighted the importance of marine organic matter on the functioning of the EML fish food-web, to which organic matter in marine sediments and likely microphytobenthos contribute most. Our study also revealed the importance of seagrass (Ruppia sp.) for detritivorous fish (i.e., Mugilidae species) and for their potential to shelter a wide variety of benthic invertebrates that are potential food sources for benthivorous fish. Our study revealed the small influence of freshwater inputs on the functioning of the EML food-web and that juvenile marine fish may use the lagoon for reasons other than feeding, most likely to avoid predation and obtain physiological advantages.